Generalized composition operators from Bloch type spaces to QK type spaces - Fang Zhang; Yongmin Liu (Journal of Function Spaces and Applications)
This paper characterizes the boundedness and compactness of the generalized composition operator (Cφgf)(z)=∫0zf'(φ(ξ))g(ξ)dξ from Bloch type spaces to QK type spaces.